THE IMPORTANT ROLE OF SHADOW TEACHER IN EMOTIONALLY GUIDING CHILDREN WITH SPECIAL NEEDS AT MUHAMMADIYAH NOTOPRAJAN PRIMARY SCHOOL YOGYAKARTA - Febriyah, Juanda; Sularso (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This article explores the important role of shadow teachers in supporting the emotional development of children with special needs (ABK) at SD Muhammadiyah Notoprajan Yogyakarta. With a game-based approach and self-reflection techniques, shadow teachers help students recognize and manage their emotions, as well as develop social skills such as communication and cooperation. This study uses a qualitative method through a literature review to understand the strategies implemented by shadow teachers. The results show that collaboration between shadow teachers, regular teachers, and parents is vital to creating an inclusive learning environment. This research provides insight for educators and policy makers to improve support for ABK, and highlights the need for ongoing training for shadow teachers.